2016
DOI: 10.1111/evo.13077
|View full text |Cite
|
Sign up to set email alerts
|

Gene duplications circumvent trade-offs in enzyme function: Insect adaptation to toxic host plants

Abstract: Herbivorous insects and their adaptations against plant toxins provide striking opportunities to investigate the genetic basis of traits involved in coevolutionary interactions. Target site insensitivity to cardenolides has evolved convergently across six orders of insects, involving identical substitutions in the Na,K-ATPase gene and repeated convergent gene duplications. The large milkweed bug, Oncopeltus fasciatus, has three copies of the Na,K-ATPase α-subunit gene that bear differing numbers of amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 64 publications
7
64
0
Order By: Relevance
“…Our results demonstrate epistasis between substitutions at sites 119 and 111/122 at the level of enzyme function. Previous studies have demonstrated increased survival of cell lines expressing Q111V, N122H, and Q111T+Q111H , and substantial insensitivity to CGinhibition despite little effect on ATPase activity for N122H, Q111T+Q111H and Q111V+Q111H (Dalla et al 2013;Dalla and Dobler 2016). Given that these substitutions were engineered on a D. melanogaster background lacking A119S, our results suggest such substitutions are likely to be associated with substantial enzyme dysfunction.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our results demonstrate epistasis between substitutions at sites 119 and 111/122 at the level of enzyme function. Previous studies have demonstrated increased survival of cell lines expressing Q111V, N122H, and Q111T+Q111H , and substantial insensitivity to CGinhibition despite little effect on ATPase activity for N122H, Q111T+Q111H and Q111V+Q111H (Dalla et al 2013;Dalla and Dobler 2016). Given that these substitutions were engineered on a D. melanogaster background lacking A119S, our results suggest such substitutions are likely to be associated with substantial enzyme dysfunction.…”
Section: Introductionsupporting
confidence: 52%
“…In all cases examined to date, species with two or more copies retain one minimally altered copy that is more highly expressed in nervous tissue, and have evolved one or more insensitive copies that are more highly expressed in the gut, the site of absorption of CGs Yang et al 2019). Further support for negative pleiotropic effects is provided by the expression of engineered ATPa1 constructs in cell lines, suggesting that some duplicate-specific CG-insensitivity substitutions appear to reduce NKA activity (Dalla and Dobler 2016). Based on these findings, the frequent parallel substitutions observed at sites 111 and 122 in specialists lacking duplicate ATPa1 copies plausibly reflect the fact that substitutions at these sites are minimally pleiotropic.…”
Section: Introductionmentioning
confidence: 99%
“…This basal level of resistance might have increased further in species adapted to feeding on cardenolide-producing plants. Physiological evidence supporting this idea has been found in several moth species (Petschenka et al, 2013), and the finding that Na/K-ATPase activity in BBB-protected neural tissue of the milkweed bug is less sensitive to cardenolides than activity in cell cultures expressing cardenolide-resistant Na/K-ATPase alleles also points to a protective effect of transporters in specialists (Dalla and Dobler, 2016). Our study provides a foundation for testing this evolutionary scenario via comparative functional genomics (Groen and Whiteman, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…), oleander ( Nerium oleander ), lily of the valley ( Convallaria majalis ) and many other plant species comprise a model system to study convergent evolution at the molecular, physiological, morphological and behavioral levels (Agrawal et al, 2012; Dobler et al, 2015; Stern, 2013; Storz, 2016). Much molecular and genetic work has focused on putatively adaptive amino acid substitutions in the Na/K-ATPase that block cardenolides from binding to this essential pump (Dalla et al, 2013; Dalla and Dobler, 2016; Dobler et al, 2012, 2015; Zhen et al, 2012). However, recent findings indicate that the amino acid substitutions in the Na/K-ATPase may not be the only adaptations to reduce sensitivity to dietary cardenolides.…”
Section: Introductionmentioning
confidence: 99%
“…If selection acts on the context-dependent expression levels of individual genes, then adaptation could be limited by epistatic interactions between regulatory mutations, as shown in elegant work on E. coli by Poelwijk et al (7). Selection on coding variants might be even more constrained, as resolution most likely requires both gene duplication and regulatory divergence (8,9).…”
mentioning
confidence: 99%